2011
DOI: 10.1177/014556131109001208
|View full text |Cite
|
Sign up to set email alerts
|

Case Report: A Branchial Cleft Anomaly Presenting as an Oropharyngeal Mass

Abstract: Branchial anomalies are common cervical pathologic entities encountered in the fi eld of otolaryngology and are typical in the pediatric and young adult populations. In most cases, these anomalies present as a cyst, sinus, or fi stula in a rather stereotypical fashion. When a branchial anomaly deviates from the classic presentation, an improper diagnosis and inadequate management are more likely to occur, leading to an increased recurrence rate. We present a case of a 6-year-old girl with an incidental fi ndin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…He also demonstrated injection techniques and, in his case, he removed the posterior pillar without doing a tonsillectomy. Thaler et al described 2 cases of branchial cleft anomalies presenting as oropharyngeal masses, both associated with the tonsillar region and Mullin and Merz presented a case involving the posterolateral oropharynx, but not associated with the tonsil, and discussed the possible embryological significance of this finding as it relates to the various theories of branchial cleft anomaly development. In 2005, Chang et al reported finding salivary gland tissue in the lower neck and postulated ectodermal heteroplasia of the precervical sinus of His.…”
Section: Discussionmentioning
confidence: 99%
“…He also demonstrated injection techniques and, in his case, he removed the posterior pillar without doing a tonsillectomy. Thaler et al described 2 cases of branchial cleft anomalies presenting as oropharyngeal masses, both associated with the tonsillar region and Mullin and Merz presented a case involving the posterolateral oropharynx, but not associated with the tonsil, and discussed the possible embryological significance of this finding as it relates to the various theories of branchial cleft anomaly development. In 2005, Chang et al reported finding salivary gland tissue in the lower neck and postulated ectodermal heteroplasia of the precervical sinus of His.…”
Section: Discussionmentioning
confidence: 99%